A nomogram model predicting the risk of postpartum stress urinary incontinence in primiparas: A multicenter study - Hong Cheng; Fuyu Gong; Yamei Shen; Ping OuYang; Ruli Ni; Hui Gao (Elsevier, 2022)
Stress urinary incontinence (SUI) is a common gynecological urinary system disease, and globally, 200 million or more people suffer from it. However, the existing literature mostly focuses on postpartum urinary incontinence (UI) or UI in middle-aged and elderly people, with little focus on primiparas. To analyse urinary incontinence prevalence and its risk factors in primiparas and establish a nomogram prediction model, 360 parturients were recruited from three hospitals between April and September 2021. A homemade electronic questionnaire was used to investigate the general demographic and perinatal characteristics of primiparas. The SUI was diagnosed by the physicians. Logistic regression analysis of independent risk factors for SUI and a nomogram prediction model were established. Ninety people were diagnosed as SUI. The number of pregnancies (OR = 3.322, 95% CI = 1.473-7.492), residence (OR = 5.451, 95% CI = 2.725-10.903), occupation (OR = 3.393, 95% CI = 1.144-10.064), education level (OR = 3.551, 95% CI = 1.223-10.308), delivery method (OR = 10.270, 95% CI = 4.090-25.789), and oxytocin use (OR = 2.166, 95% CI = 1.142-4.109) were independent risk factors for SUI. The C-index of the nomogram prediction model was 0.798 (95% CI = 0.749-0.846). The POPDI score, CRADI score, UDI score, and PFDI scores of women with SUI were significantly higher than those of non-SUI women, while I-QOL scores were significantly lower than those of non-SUI women. In conclusion, the prevalence of SUI among primiparas in Fuyang, China, was 25.00%, which exhibited a large impact on the quality of life of puerperae. The present study successfully established an individualized nomogram prediction model of SUI for primiparas with good discrimination and diagnostic efficiency, which was helpful for the early clinical identification of high-risk primiparas with SUI.